2020
DOI: 10.1038/s41438-019-0236-1
|View full text |Cite|
|
Sign up to set email alerts
|

A universal pipeline for mobile mRNA detection and insights into heterografting advantages under chilling stress

Abstract: Heterografting has long been used to enhance the chilling tolerance of temperature-sensitive crops, including watermelon, whose mechanism is known to involve bidirectional long-distance mRNA movements. Despite several studies reporting on mobile mRNA (mb-mRNA) profiles in plants, accurate identification of mb-mRNAs is challenging owing to an array of technical problems. Here, we developed a bioinformatical pipeline that took most of the known technical concerns into consideration and is considered to be a univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Similarly, Liu et al reported the differential expression of 787 genes between watermelon homo and heterograft (bottle gourd rootstock) 16 . To highlight the importance of bottle gourd as rootstock, Wang et al (2020) analyzed the transcriptome of bottle gourd (rootstock) and watermelon (scion) under chilling reatment. They reported that bottle gourd homograft, as well as hetero-graft, are tolerant to chilling stress compared to the water-melon homograft 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Liu et al reported the differential expression of 787 genes between watermelon homo and heterograft (bottle gourd rootstock) 16 . To highlight the importance of bottle gourd as rootstock, Wang et al (2020) analyzed the transcriptome of bottle gourd (rootstock) and watermelon (scion) under chilling reatment. They reported that bottle gourd homograft, as well as hetero-graft, are tolerant to chilling stress compared to the water-melon homograft 50 .…”
Section: Discussionmentioning
confidence: 99%
“…(2020) analyzed the transcriptome of bottle gourd (rootstock) and watermelon (scion) under chilling reatment. They reported that bottle gourd homograft, as well as hetero-graft, are tolerant to chilling stress compared to the water-melon homograft 50 . Thus, in-depth analysis of GRAS transcription factors in the bottle gourd genome will be helpful for enhancing the use of bottle gourd as valuable rootstock material and could also be extended in other vegetable crops.…”
Section: Discussionmentioning
confidence: 99%
“…The homologous mRNA AtCK1 (At1G71697) was confirmed to have bidirectional mobility in grafted A. thaliana [ 25 ]. Thus, directional mRNA movement is independent of RNA abundance, RNA motifs, and mRNA length [ 44 ]. On the one hand, mRNA movement direction is dependent on the target tissue where the mRNA functions and the biological processes in which they participate.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the actual research materials used are often different from those used for reference genome sequencing, resulting in many false positives and partial false negatives in bioinformatics analysis. In the study by Wang et al (2020), an important improvement in the pipeline was the inclusion of a step to correct for SNPs and indels between the experimental and reference genomes. Here, we developed a stringent bioinformatics pipeline based on the method published by Wang et al (2020) that takes most of the known technical concerns into consideration.…”
Section: Methods For the Identification Of Mobile Mrnas And Proteinsmentioning
confidence: 99%